Analisis Kesalahan Berbahasa Indonesia dalam Surat Dinas di Kecamatan Sindangkasih - Fauziah hindasah, Astri; Nazwa Azizah Genuita; Risqi Sri Mulyati; Ichsan Fauzi Rachman (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
A letter is a means of conveying information in writing from one party to another. Then there are elements that fall into the category of Indonesian language errors in this letter, namely errors in using letters, errors in writing words, errors in writing punctuation marks, ineffective use of words. Errors in correspondence made by writers do not refer to letter writing standards, based on the letter writers' knowledge and skills regarding grammar and limited letter form. The location of this research is the Sindangkasih sub-district office, Ciamis Regency. The aim is to improve letter writing in agencies because there is a habit where writers only rely on samples without following new rules. The research method used in this research is descriptive analytical method. The sampling carried out was comparing three letters as material for research. The results obtained from the research and analysis on the effectiveness of sentences were six errors from the 3 letters, and in spelling errors there were nine errors from the 3 letters.